ChemInform Abstract: Facile Access to Benzothiophenes Through Metal‐Free Iodine‐Catalyzed Intermolecular Cyclization of Thiophenols and Alkynes. Issue 1 (17th December 2015) - Yan, Kelu; Yang, Daoshan; Zhang, Mengqi; Wei, Wei; Liu, Yao; Tian, Laijin; Wang, Hua
Abstract: A novel and green method for preparation of benzothiophenes is developed.